HUBUNGAN ANTARA KERAGAMAN TUNGAU FAMILI Macrochelidae (ACARI: MESOSTIGMATA) DAN FAKTOR LINGKUNGAN PADA MANUR AYAM PEDAGING DENGAN TIPE KANDANG PEMELIHARAAN BERBEDA - Nurhadi Eko Firmansyah; Bambang Heru Budianto; Hery Pratiknyo (Scripta Biologica, 2019)
Livestock of broiler chickens using several types of cages, including the type of litter stage and litter postal. Treatment of chicken manure in both types of cages will cause the condition of the manure as the habitat of mite family Macrochelidae will be different. The diversity of mites family Macrochelidae are suspected to be different in manure found on stage litter cages compared to litter postal cages and influenced by some environmental factors. The aim of this study is to analyze the diversity of mites family Macrochelidae and its relation to environmental factors. The obtained manure sample was then taken to the laboratory and placed on a modified Barlese-Tullgren for mite isolation. The mites obtained are then counted, preserved, and identified at the Laboratory. Environmental factors measured are temperature and humidity. The diversity data obtained were analyzed using the Shannon-Wiener index and the Shannon-Evennes index. Pearson correlation test to determine the relationship between temperature and humidity to the diversity of mites of Macrochelidae family. Five species of mite Macrochelidae are Macrocheles sp.1, Macrocheles sp.2, Glyptholaspis sp., Neopodocinum sp., Holostaspella sp. The diversity index of mites family Macrochelidae on manure litter stage is 0.81354. The index diversity of mites on manure litter postal is 0.79871. The humidity factor influences the diversity of the mites of family Macrochelidae in both types of cages.